THE EFFECT OF GAMIFICATION BASED ON BALINESE LOCAL STORY - Dio Aditya; Putu Kerti Nitiasih; Luh Gd Rahayu Budiarta (Universitas Muhammadiyah Kalimantan Timur, 2020)
This research aimed to know the significant effect of Gamification based on Balinese Local Story toward students’ listening comprehension. The implementation of one group pretest posttest was a design for collecting the data. The pretest and posttest was in the form of multiple choice tests. The research population consisted of 164 students of SD Negeri 2 Anturan. Then, the research sample was 5th grade students who consisted of 21 students. The result of the data presented that, there was significance different score between pretest and posttest. The mean score of pretest was 43.37. In contrast, the mean score of posttest was 79.74. Based on the results, the mean score of posttest was higher than pretest. The result of effect size was 3.190 that means to large effect. The result of effect size showed Gamification based on Balinse local story could improve students’ listening comprehension.